GAMBARAN HASIL PEMERIKSAAN TROMBOSIT DARAH PADA PENDERITA DBD SESUDAH MENGKONSUMSI JAMBU BIJI (psidium guajava) DI RST SOLOK TAHUN 2018 - Marisa, Marisa; Suriani, Endang (IAIN Batusangkar, 2019)
Dengue or dengue fever is the most dominant disease suffered by the people of Indonesia. It can be detected through hematocrit values and platelet counts of patients. Usually, the patient's hematocrit value increases and blood plasma volume decreases. On the other hand, the platelet count of the patient decreases due to bone marrow suppression and the presence of antibodies against platelet deficiency. The purpose of this study was to determine the hematocrit value and platelet count of patients with dengue fever. This study was conducted on 10 patients with dengue fever at the Solok Army Hospital in the December 2018 - January 2019 period. The results of this study found that the total platelet count of patients when starting treatment was 38,300 cells / mm3. While the mean hematocrit when starting treatment is 43.5%. It can be concluded that dengue fever sufferers have increased hematocrit values and decreased platelet counts.